Sensible Use(rs) and the Construction of Self-Identity in Research Interviews - Martijn Huisman; Eduard Cuelenaere; Stijn Joye; Daniël Biltereyst (University of Zurich, IKMZ - Department of Communication and Media Research, 2021)
As a much-used data collection method in qualitative research, interviewing is a primary way to make sense of social life. However, critics point out that interviews are often used uncritically and unreflectively, without considering epistemological foundations and self-presentation efforts by interviewees. By way of a two-step, theory-driven qualitative thematic analysis, this study examines how Belgian middle-aged and older adults (51-79 years old) construct their self-identity in research interviews as sensible internet users with regards to online health information (OHI) and their motivations for doing so. The findings are underpinned by a theoretical framework which enhances impression management (IM) theory with the third-person effect (TPE). The study finds that respondents engage in various IM behaviours, including instances of the TPE, to maximise positive impressions and minimise negative impressions. Through IM, interviewees 1) respond to critical questions; 2) proactively demonstrate knowledge, accomplishments, and positive outcomes; 3) compare and distance oneself from others; and 4) communicate limitations and offer external explanations. The findings contribute to the scant literature on IM in research interviews and among older adults and carry various implications for the field of health communication and beyond, such as the importance of critically reflecting on interviewing and going beyond the face value of the data.